Carbon Nanotubes in Liquid Media: Influence of Solvation on the Colloidal Stability - Haidar, Vladislav; Skliarova, Kseniia; Karbivskii, Volodymyr; Kryshtal, Oleksandr; Bogatyrenko, Serhii; Mchedlov-Petrossyan, Mykola (V. N. Karazin Kharkiv National University Bulletin. Chemical series, 2026)
This article presents the results of a study of the colloidal properties of multiwalled carbon nanotubes (MWCNTs) in water and two organic solvents. This work continues the systematic study of the aggregation stability and coagulation of carbon nanoparticles in various solvents with the aim of identifying the contribution of solvation to the colloidal properties of these widely used systems. The samples were characterized by EDS and XPS methods. The suspension was prepared using ultrasonic treatment in N-methyl-pyrrolidin-2-one and diluted 100-fold with water, acetonitrile, or dimethyl sulfoxide. The working concentration of MWCNTs carbon nanotubes was 5×10–4 g L–1. The size of negatively charged particles in water, 95 vol% aqueous CH3CN, and 95 vol% DMSO was determined by dynamic light scattering: the Zaver values ​​are 249±15, 265±42 and 146±8 nm, respectively, which corresponds to the diameter of the equivalent sphere. TEM images show that the CNT diameter in aqueous suspension is approximately 9–11 nm and the length is approximately 40–170 nm. Critical coagulation concentrations (CCC) of NaCl were determined using the Fuchs function. These values ​​differ significantly in water and 95% acetonitrile: CCC = 230 and 1.0 mM, respectively. In 95% DMSO, coagulation is less pronounced. The effects were discussed in terms of Gutmann’s Donor Numbers for organic solvents and the specificity of hydration of non-polar materials in water. The CCC of HCl in water is 1.5 mM, which suggests the role of acid-base properties in the formation of the negative charge of the MWCNT colloidal particles.